2019
DOI: 10.1039/c8cp06716c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo simulations of organic ferroelectrics

Abstract: Ferroelectrics find broad applications, e.g. in non-volatile memories, but the switching kinetics in real, disordered, materials is still incompletely understood. Here, we develop an electrostatic model to study ferroelectric switching using 3D Monte Carlo simulations. We apply this model to the prototypical small molecular ferroelectric trialkylbenzene-1,3,5-tricarboxamide (BTA) and find good agreement between the Monte Carlo simulations, experiments, and molecular dynamics studies. Since the model lacks any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…S13 (ESI †), that show highly ordered directional stacks for the mixtures with a characteristic length scale that is in between the pure linear and branched compounds. The 1 : 1 mixtures having middling characteristics prove that the improvement is linear and no amplification effects, previously demonstrated in diluted solutions of branched-chiral and linear-achiral BTAs mixtures, 50,51 are present in our random stereochemistry mixtures in the solid-state.…”
Section: Mixtures Of Linear and Branched Btassupporting
confidence: 76%
See 1 more Smart Citation
“…S13 (ESI †), that show highly ordered directional stacks for the mixtures with a characteristic length scale that is in between the pure linear and branched compounds. The 1 : 1 mixtures having middling characteristics prove that the improvement is linear and no amplification effects, previously demonstrated in diluted solutions of branched-chiral and linear-achiral BTAs mixtures, 50,51 are present in our random stereochemistry mixtures in the solid-state.…”
Section: Mixtures Of Linear and Branched Btassupporting
confidence: 76%
“…Cornelissen et al have demonstrated by kinetic Monte-Carlo simulations that structural disorder has a much stronger impact on the depolarization rate than on the coercive field value. 50 Therefore, a lower level of structural and energetic disorder allows for significant improvement in polarization retention with only a slight increase in the concomitant coercive field value. These principles hold for blends of linear and branched BTAs, that are discussed further, as well.…”
Section: Box Switchingmentioning
confidence: 99%
“…For the thermally activated nucleation limited switching mechanism, a greater critical domain size would lead to a higher depolarization E a and, in turn, to a longer retention time. This was also in line with the subsequent simulation results produced by the same authors . In addition to the room temperature operation, and fast switching, this BTA compound could be considered as a practical ferroelectric columnar LC.…”
Section: Columnar Lcs Based On Amide Derivativessupporting
confidence: 86%
“…This could suggest that the shorter homologs have the ability to enhance the long‐range intermolecular cooperation, resulting in the cumulative effect of the molecular dipole moments and, in turn, higher P s value. The authors confirmed the above experimental result by using a Monte‐Carlo simulation …”
Section: Columnar Lcs Based On Amide Derivativessupporting
confidence: 69%
“…More recently Kemerink and coworkers developed an electrostatic model that was used as basis for 3D kinetic Monte Carlo simulations in order to describe switching kinetics in these ferroelectrics. 521 The authors found that in the case of spontaneous polarization reversal, nucleation occurs at defects, which are caused by disorder. In contrast, in the field-driven reversal, nucleation occurs at the electrodes.…”
Section: Defects In Supramolecular Polymersmentioning
confidence: 99%